2005
DOI: 10.1021/ja052175k
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Intramolecular Selenocarbamoylation of Alkynes with Carbamoselenoates:  Formation of α-Alkylidene-β-lactam Framework

Abstract: Pd-catalyzed intramolecular selenocarbamoylation of alkynes leading to alpha-alkylidene-beta-lactams was developed. This reaction can be applied to thiocarbamoylation and to the synthesis of delta- and epsilon-lactams and a cyclobutanone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(34 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…Such ligands promote oxidative addition to the acyl chlorine bond by increasing the nucleophilic nature of Pd(0) and also favour the reductive elimination step [16]. Others have recently reported a closely related process affording a-alkylidene-b-lactams [17].…”
Section: Carbamyl Chloride Starter Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such ligands promote oxidative addition to the acyl chlorine bond by increasing the nucleophilic nature of Pd(0) and also favour the reductive elimination step [16]. Others have recently reported a closely related process affording a-alkylidene-b-lactams [17].…”
Section: Carbamyl Chloride Starter Speciesmentioning
confidence: 99%
“…[180][181][182]75.60;H,4.95;N,4.30. C 20 H 15 NOS requires: C,75.70;H,4.75;N,4.40%); m max /cm À1 1653, 1595, 1408, 1286, 1216and 1203d H (250 MHz), 7.64 (d, J = 7.4 Hz, 1H, ArH), 7.49-7.24 (m, 10H, ArH/@CH), 7.19 (dd, J = 7.3, 0.5 Hz, 1H, ArH), 7.06 (dd, J = 5.1, 3.7 Hz, 1H, furyl H) and 4.86 (s, 2H, NCH 2 Ar); m/z (%) 318(M + H + , 100), 288(26) and 207 (17).…”
Section: (3z)-1-benzyl-3-(2-thienylmethylene)-13-dihydro-2h-indol-2-mentioning
confidence: 99%
“…For example, we have reported that carbamoselenoates 1 having a terminal alkynyl moiety on the nitrogen atom underwent selenocarbamoylation of alkynes intramolecularly with high regio‐ and stereoselectivities to afford four‐ to eight‐membered lactams 2 having an exocyclic double bond in high yields by the use of Pd(PPh 3 ) 4 as a catalyst (Eq. ) . The treatment of vinylselenides 3 having a alkynylmethyl group on the nitrogen atom with Pt(PPh 3 ) 4 afforded six‐membered lactam frameworks 4 or 5 having a dienone unit by cis ‐vinylselenation of alkynes (Eq. )…”
Section: Introductionmentioning
confidence: 99%
“…From the different classes of organochalcogen compounds, vinylic chalcogenides constitute a very useful group and have attracted considerable attention in recent years as synthetic precursors [14][15][16]. Many vinylic sulfide, selenide and telluride preparations involve the use of expensive catalysts or starting materials that are not readily available or the products are obtained as mixtures of regio or stereoisomers [17][18][19][20][21][22][23][24][25][26]. There is still a lack of simple, efficient methods for their preparation.…”
Section: Introductionmentioning
confidence: 99%